2017
DOI: 10.1017/aaq.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Models, Niche Construction, and the Eastern Agricultural Complex

Abstract: Some proponents of niche construction challenge the validity of optimality models for investigating agricultural origins, but offer no alternative strategy for understanding the economic context of human foraging decisions. They refer to the Eastern Agricultural Complex as an example of how seed cultivation can result from resource enhancement rather than population-induced resource depression, contradicting a prediction inferred from the prey choice model. Low-return seed cultigens were harvested in environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Indeed, NCT has provided useful concepts, insights, and criticisms for anthropologists and archaeologists (Bird et al 2013; Bird et al 2016; Broughton et al 2010; Laland and O'Brien 2010, 2012; O'Brien and Laland 2012). Many also recognize its importance in understanding domestication and promote its use in conjunction with OFT models (Broughton et al 2010; Gremillion et al 2014; Mohlenhoff and Codding 2017; Stiner and Kuhn 2016; Zeanah 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, NCT has provided useful concepts, insights, and criticisms for anthropologists and archaeologists (Bird et al 2013; Bird et al 2016; Broughton et al 2010; Laland and O'Brien 2010, 2012; O'Brien and Laland 2012). Many also recognize its importance in understanding domestication and promote its use in conjunction with OFT models (Broughton et al 2010; Gremillion et al 2014; Mohlenhoff and Codding 2017; Stiner and Kuhn 2016; Zeanah 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It suggests instead that the mitigation of risk caused by environmental variability was a more likely cause of domestication in the region (Gremillion 2002, 2004). Additionally, Zeanah (2017) modeled foraging decisions surrounding initial domestication in eastern North America and found that small-seed exploitation can be advantageous when high-ranking hickory nuts are not readily available, due to either poor yields resulting from natural environmental variability or restricted access to profitable but distant hickory-nut patches as a result of population packing. Zeanah provided archaeobotanical data documenting subsistence intensification prior to the widespread adoption of horticultural economies, although he did not address whether intensification preceded the earliest evidence of plant domestication in the region.…”
mentioning
confidence: 99%
“…This research draws primarily on human behavioral ecology and more recently on niche construction theory to investigate human-environment relationships following the adoption or development of domesticated plants and animals. While practitioners debate the utility of these perspectives (Codding and Bird 2015; Gremillion, Barton, and Piperno 2014; Smith 2015; Zeanah 2017; Zeder 2012, 2015a) or attempt to engage with both frameworks (Mohlenhoff, Brenner, and Codding 2015; Steiner and Kuhn 2016; however, see Zeder 2014, 2015b), recent complementary research highlights how anthropogenic and natural environmental disturbance factors can influence the long-term trajectory of farming and foraging practices (Bird, Bliege Bird, and Codding 2016; Bliege Bird 2015; Codding et al 2014; Lightfoot et al 2013). Furthermore, both perspectives also identify risk as a significant factor influencing the decision-making of farmers and foragers (Kelly 2013:68–69; Winterhalder and Kennet 2006; Zeder 2012:251).…”
mentioning
confidence: 99%
“…The case of the Taiwan Neolithic offers an opportunity to examine reference information about foraging niches from a mountainous island habitat. Assembling reference knowledge about processes that are germane to, but independent of, past phenomena of interest can complement limited evidentiary data to help guide archaeological research questions [20,29,[62][63][64]. Behavioral ecology concept models can be informative about the dynamics at the level of the individual, and assist in the development of hypotheses about systems that can be assessed with archaeological data.…”
Section: Quaternary 2020 3mentioning
confidence: 99%